Epilepsy and Molecular Phenotype Affect the Neurodevelopment of Pediatric Angelman Syndrome Patients in China - Li, Shuang; Ma, Yu; Wang, Tianqi; Jin, Huimin; Du, Xiaonan; Wang, Yi (Frontiers in Psychiatry, 2022)
Objective: This study investigated the mental development of children with Angelman syndrome (AS) in China and evaluated the impact of molecular subtype, age, epilepsy, and sex using the Chinese version of the Griffith Mental Development Scale (GMDS-C) to provide detailed baseline data regarding neurodevelopment with AS in China. Methods: Participants were recruited from the AS Natural History Study. The GMDS-C was used to evaluate the mental age and developmental quotients of all participants. The general quotient (GQ) and quotients of five subscales (sports, personal-social, auditory language, eye-hand coordination, and comprehensive performance) were calculated. Results: A total of 119 children (average age: 42.12 months; range, 7.5-95.5 months) with a genetic diagnosis of AS were enrolled. The median GQ score of the GMDS was 29.6 points (95% confidence interval, 28.6-33.25). The children had relatively good locomotor and personal-social skills but poor language skills. Overall, 89% (106/119) had mental ages younger than 24 months for all five subscales. The non-deletion group (i.e., without deletion in chromosome 15q11-13) had higher GQs and locomotor, personal-social, and performance subscale quotients. The GQ was significantly different among the three age subgroups and significantly correlated with age. Compared with the non-epilepsy group, the epilepsy group had lower GQs and lower quotients for the locomotor, personal-social, speech, language, and eye-hand coordination subscales. Conclusion: Children with AS in China experience progressive neurodevelopmental deterioration. In addition to age, molecular subtypes and the onset of seizures may affect the intellectual development of these patients. The GMDS-C is an accurate tool that can assess the clinical characteristics of AS. The data of this study can be used as baseline data for clinical trials performed to evaluate drug development or other AS treatment development.